2016
DOI: 10.4172/2155-6148.1000622
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Effect of Propofol, Etomidate and Propofol Plus Etomidate Induction on Hemodynamic Response to Endotracheal Intubation: A RCT

Abstract: Objective: The primary objective of this study was to compare the efficacy of 3 different anesthesia induction approach (Inj. Propofol, Inj. Etomidate and Inj. propofol plus Inj Etomidate) in maintaining hemodynamic stability during induction and following endotracheal intubation in elective surgery. Material and method:Ethical committee clearance taken, 90 patients aged 15 to 60 years of either sex and ASA physical status I or II scheduled for elective surgery under general anesthesia were taken for study. Wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
(22 reference statements)
3
7
0
Order By: Relevance
“…1,2,14 There are various studies which have compared the haemodynamic variations with propofol and etomidate following induction and endotracheal intubation. Similar to our finding, Meena K et al 16 showed that heart rate decreased after induction but increased after laryngoscopy and intubation and the increase with the etomidate group was statistically significantly higher than that of propofol. Their study also showed a significant decrease in arterial blood pressure after induction with propofol which did not increase above baseline value after intubation while with etomidate, there was a significant increase in arterial pressure following intubation, hence showing better haemodynamic condition with etomidate as compared to propofol.…”
Section: Discussionsupporting
confidence: 92%
“…1,2,14 There are various studies which have compared the haemodynamic variations with propofol and etomidate following induction and endotracheal intubation. Similar to our finding, Meena K et al 16 showed that heart rate decreased after induction but increased after laryngoscopy and intubation and the increase with the etomidate group was statistically significantly higher than that of propofol. Their study also showed a significant decrease in arterial blood pressure after induction with propofol which did not increase above baseline value after intubation while with etomidate, there was a significant increase in arterial pressure following intubation, hence showing better haemodynamic condition with etomidate as compared to propofol.…”
Section: Discussionsupporting
confidence: 92%
“…8 Combination of different induction agents has been used in the past which cause an evident decrease in anaesthetic, better sedation and amnesia, decreased side effects and reduce cost. 10 Demographic profile with respect to age, sex and weight were comparable in both the groups and consistent with the study by K Meena et al with age group (p=0.178) and gender distribution (p=0.241). 2 Statistically significant difference was found in heart rate, SBP, DBP and MAP in both the groups at 0 min and after 1 minute of induction with hemodynamic parameters significantly higher in etomidate group than the etofol group but did not require any clinical intervention.…”
Section: Discussionsupporting
confidence: 91%
“…There has been search of an ideal induction agent that is haemodynamically stable during laryngoscopy and without side effects since the advent of anaesthesia. 10 Thiopentone, Etomidate, Propofol, Midazolam, and Ketamine are the commonly used induction agents. 11,12 There are concerns regarding smooth induction and emergence from anaesthesia with thiopentone, midazolam and ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…1 A combination of propofol and etomidate was found to be better than either propofol or etomidate alone when used for induction during general anesthesia. 2 The primary concern with the use of propofol is hypotension. It was shown that propofol causes a 34% reduction in mean arterial pressure-time integral from the baseline after induction when compared with etomidate, despite the use of vasopressors.…”
Section: How Does Propofol Fare When Compared With Other Agents?mentioning
confidence: 99%